The relationship between transformative leadership and self efficacy of faculty members K.N.T.U - asghar zamani; mahtab pouratashi (Allameh Tabataba'i University Press, 2016)
The relationship between transformative leadership and self efficacy of faculty members K.N.T.U. Abstract: The aim of this study was to investigate the relationship between transformational leadership style and self-efficacy of K.N.T. University faculty members. the research method was correlation .the statistical population included all faculty members of K.N.T University (N= 304). 170 faculty members were selected, using Kerjesi and Morgan Table. For sampling, random sampling method was used. A questionnaire was used for data collection of faculty members. Its validity confirmed by views of faculty members and its reliability confirmed by conduction Cronbach's alpha. Data were analyzed using SPSS and test such as Pearson correlation coefficient and multiple regression analysis were conducted. Results showed that there were significant correlations between components of transformational leadership style (idealized influence, inspirational motivation, intellectual stimulation and individualized consideration) with self-efficacy of faculty members. regression analysis showed that among predictive variables, idealized influence had the most role in predicting self-efficacy of faculty members. Keywords: Transformational Leadership, self efficacy, idealized influence, intellectual stimulation, inspirational motivation, personal considerations